2011
DOI: 10.1371/annotation/4eeebe50-1b31-422c-94a0-effcf9eda85f
|View full text |Cite
|
Sign up to set email alerts
|

Correction: In Vitro Acute Exposure to DEHP Affects Oocyte Meiotic Maturation, Energy and Oxidative Stress Parameters in a Large Animal Model

Abstract: Phthalates are ubiquitous environmental contaminants because of their use in plastics and other common consumer products. Di-(2-ethylhexyl) phthalate (DEHP) is the most abundant phthalate and it impairs fertility by acting as an endocrine disruptor. The aim of the present study was to analyze the effects of in vitro acute exposure to DEHP on oocyte maturation, energy and oxidative status in the horse, a large animal model. Cumulus cell (CC) apoptosis and oxidative status were also investigated. Cumulus-oocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Similarly, some EDCs were linked to decreased fertility and diminished ovarian reserves in women [30][31][32][33][34]. Animal studies confirmed that EDC exposure can affect mammary gland and uterine development, both in terms of timing and in terms of morphological changes and in silico analyses contributed to predict the mechanics behind this [16,35,36].…”
Section: Endocrine Disruptors and Human Healthmentioning
confidence: 89%
See 1 more Smart Citation
“…Similarly, some EDCs were linked to decreased fertility and diminished ovarian reserves in women [30][31][32][33][34]. Animal studies confirmed that EDC exposure can affect mammary gland and uterine development, both in terms of timing and in terms of morphological changes and in silico analyses contributed to predict the mechanics behind this [16,35,36].…”
Section: Endocrine Disruptors and Human Healthmentioning
confidence: 89%
“…The most commonly used phthalate however, di-2-ethylhexyl phthalate (DEHP) have been linked with endocrine disrupting effects on the reproductive system due to his action as an androgen antagonist. DEHP has been correlated to lower fertility and sperm motility in males [90], to defective oocyte maturation [30,123], to anomalies in sexual development [122], to asthma [25], to breast cancer induction and to a wide range of other endocrine effects [124]. Recently, DEHP was categorized as a non-persistent endocrine disrupting compound by the world health organization (WHO).…”
Section: Phthalates and Perfluorinated Chemicalsmentioning
confidence: 99%
“…There are two main ways in which sperm can encounter unmetabolized DEHP: via abrupt release from adipose tissue or through release from medical devices, such as a urological catheter-making unmetabolized DEHP a prominent threat to sperm fertility. DEHP exposure has been previously linked to increased ROS production in somatic cells and oocytes (Wu et al 2014;Tripathi et al 2019;Kim et al 2013;Ambruosi et al 2011). However, its impact on ROS over-production in sperm was not elucidated.…”
Section: Discussionmentioning
confidence: 99%